2018
DOI: 10.7717/peerj.5772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of incisional complications between skin closures using a simple continuous or intradermal pattern: a pilot study in horses undergoing ventral median celiotomy

Abstract: BackgroundDevelopment of incisional complications following ventral median celiotomy might depend on suture pattern for skin closure.MethodsIn this prospective study, 21 healthy male horses underwent celiotomy. Skin closure was either performed via a continuous percutaneous pattern (CO group; 5 warmbloods/5 ponies) or an intradermal pattern (ID group; 5 warmbloods/6 ponies). Follow-up examination of the incisional site included daily monitoring for edema, dehiscence, and drainage. Transcutaneous ultrasound was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
1
14
1
1
Order By: Relevance
“…25 Wound dehiscence concerns have caused some surgeons to recommend a subcuticular layer that is then overlaid with cyanoacrylates to provide a waterproof sealant, similarly to what is reported in our study. 25 Furthermore, authors from previous equine laparotomy studies 30,31 have reported lower prevalence of incisional complications when avoiding a percutaneous pattern. 28,29 Even though an intradermal or subcutaneous layer may provide sufficient apposition, additional strength is provided by incorporating cyanoacrylate to the closure, without compromising the skin barrier.…”
Section: Discussionmentioning
confidence: 97%
“…25 Wound dehiscence concerns have caused some surgeons to recommend a subcuticular layer that is then overlaid with cyanoacrylates to provide a waterproof sealant, similarly to what is reported in our study. 25 Furthermore, authors from previous equine laparotomy studies 30,31 have reported lower prevalence of incisional complications when avoiding a percutaneous pattern. 28,29 Even though an intradermal or subcutaneous layer may provide sufficient apposition, additional strength is provided by incorporating cyanoacrylate to the closure, without compromising the skin barrier.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of abdominal closure technique on incisional complications has been extensively studied (Anderson et al, 2015; Biedrzycki & Brounts, 2016; Bischofberger et al, 2010; Colbath et al, 2014; Coomer et al, 2007; Darnaud et al, 2016; Isgren et al, 2017; Kilcoyne et al, 2019; Magee & Galuppo, 1999; Mair & Smith, 2005; Rinnovati et al, 2016; Salem et al, 2016; Scharner et al, 2017, 2018; Smith et al, 2007; Torfs et al, 2010; Verkade et al, 2020). The standard abdominal wall closing technique includes 3 layers, linea alba (LA), subcutaneous (SC) and skin.…”
Section: Surgical Site Infectionmentioning
confidence: 99%
“…However, by the commonly used strict definition, any surgical abdominal wound draining over 24 h after colic surgery is considered infected (Colbath et al, 2014;Kilcoyne et al, 2019;Scharner et al, 2018, Torfs et al, 2010. It has been postulated that there is a marked underestimation of the prevalence of SSIs after colic surgery.…”
Section: Surg Ic Al S Ite Infec Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of hernias can be associated with injuries. Often the occurrence of hernias can be associated with anatomical conditions that most often occur in the navel, groin or perineum (Shnjakina and Shherbakov, 2008;Gimranov andLjukovec, 2010, 2011;Safonov, 2018), or they may arise as a result of unsuccessful operations or their complications (Scharner et al, 2018;Winter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%